BaZrxTi1−xO3 Epitaxial Thin Films for Electrocaloric Investigations. Issue 8 (16th July 2018) - Engelhardt, Stefan; Molin, Christian; Gebhardt, Sylvia; Fähler, Sebastian; Nielsch, Kornelius; Hühne, Ruben
Abstract: Epitaxial BaZr x Ti1− x O3 (BZT) thin films with a Zr content between x= 0 and x= 0.3 are grown by pulsed laser deposition on (001)‐oriented SrTiO3 single crystals utilizing a conducting SrRuO3 buffer layer and Pt top electrodes. An undisturbed epitaxial growth with a smooth and homogeneous surface structure is obtained for all Zr containing films, whereas some preferentially growing grains and twins are observed for pure BaTiO3 films. Temperature‐dependent measurements of the relative permittivity suggest a diffuse phase transition. The temperature of the maximum permittivity as well as the electrical polarizability at room temperature decrease with increasing Zr content. The observed frequency dependence suggests relaxor ferroelectric properties for all Zr‐containing films. The indirectly determined electrocaloric responses are considerably lower compared to thick films, which is primarily attributed to the diffuse character of the phase transition. A maximum adiabatic temperature change of about 0.3 K for an electric field change of 170 kV cm −1 is found for BaZr0.2 Ti0.8 O3 . Abstract : BaZr x Ti1− x O3 epitaxial thin films are grown using pulsed laser deposition to investigate the interplay between the electrocaloric (EC) effect and microstructure in this lead‐free material system. The grown thin films exhibit a broad permittivity maximum, which suggests a diffuse phase transition. The indirectly determined EC responses are low in value but increase with temperature over a wide temperature range.